PSYCHOLOGICAL STRESS MONITORING USING INVASIVE AND NON-INVASIVE METHODS IN ATHLETES - Makra, Gabriella; Balogh, László (Stadium - Hungarian Journal of Sport Sciences, 2021)
Introduction: The quality of performance is essential both in everyday life and in competition. In sports science (also), we have to think of the man in a complex way as a bio-psycho-social unit. In addition to changes in ECG HR and blood cortisol levels, gastrointestinal tract movements are also associated with stress management (FUKUNAGA et al., 2000) (VIANNA - TRANEL, 2006), which plays a crucial role in determining the quality of performance. Several preclinical trials have formed the basis of our research (SZŰCS et al., 2018).Objective: Based on our earlier research and literature reviews, we would like to test and participate in validating a new method that can monitor the effects of stress on humans in real-time, in a non-invasive way, with quantitative results. In addition to GI monitoring, cortisol levels are measured invasively in the subjects, so we hope to obtain complex results.Methods: n = 13, athletes, male = 11, female = 2, mean age 22 +/- 1,031 years. Our protocol was 115 minutes, in which we distinguished four stages (rest, stress, latency 1, latency 2). We use two methods to measure stress. One is the blood cortisol level (ELISA), and the other is the MDE Heidelberg Stress Holter (EGG), which is an innovative measurement tool capable of simultaneously examining several parameters (Small Intestine, Colon, Stomach, ECG HR). The VTS DT package was used as a stressor.Result: Based on the complex results of the EGG, we can conclude that the Small Intestine, Colon, and Stomach motility, as assessed by the Power Spectrum (PS) Fold Change (FC) calculation, increased together under stress, and then latency decreased together over time. However, the rate of change in cortisol levels showed that most participants adapted the stressor as eustress so that its value decreased linearly.Conclusions: Innovative measurement and evaluation methods are well utilized, as they can communicate many measurement data in a valid, real-time, non-invasive way, with a parallel display. These data and results will be used in athlete selection, mental training, elite sports, neuro-biofeedback, and health preservation.